Counseling Management Garbage in the Village Banjarharjo - Shokheh, Mukhamad; Soliah, Shinta Okbiantari; Nugraha, Alexander Dismas Fajar; Nugroho, Farras Nafalya Atha; Farikah, Fadia Nur; Irfanudin, Dimas Veri; Alfiana, Nokha; Topan, Bima Ali; Dewi, Rina Novita; Kurniasari, Diah Dwi; Widiastuti, Apriliana; Janah, Ita Nur; Aisyah, Chilmi Nour (Universitas Negeri Semarang, 2023)
Village Banjarharjo located at an average altitude of 300 meters on surface sea. By topography village This is plain with land vast rice fields. Village area about 150 hectares and divided into 3 parts ie settlements, moorlands and forests, and rice fields. Village Banjarharjo Still faced with problem rubbish. Still many which citizens throw away rubbish haphazard. Therefore That Student Unnes Enterprising 5 doing socialization management rubbish together Service Environment Life as effort For overcome problem the. Activity program implementation counseling management rubbish for inhabitant Village Banjarharjo is encouraged student Unnes Activity 5 is carried out on the day Monday, July 31 2023 in the Hall Village Banjarharjo. Destination from activity that is the first to appear awareness public For sort waste, manage waste, and make use of it return so that environment they can free from waste and the environment become beautiful. Second, with exists management rubbish so can reduce amount trash is a must stockpiled on site Final Processing (TPA). And third For increase understanding and knowledge public in management rubbish become mark economical through establishment of a waste bank in the village Banjarharjo Method used in study This that is qualitative with do observation or observation in a way direct. Result of devotion This that is public become know better management waste and the formation of waste banks.